2020
DOI: 10.22543/7674.72.p250256
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical pattern– a prognostic factor for synchronous gastrointestinal cancer

Abstract: Recent advancements in medical genetics and molecular biology are reflected in the modern understanding and approach to colorectal carcinoma (CRC). Understanding the cellular mechanisms and mutational patterns that promote carcinogenesis could enhance the predictive accuracy of the TNM classification. Furthermore, this will allow for a much more documented stratification and tailored oncological treatment. This paper presents an illustrative case of a relatively young patient (50 years old) with no family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The microbiome is different (39)(40)(41), and recently published data has shown that colorectal cancerassociated bacterial clusters are differentially correlated with mucosal gene expression profiles, while a few clusters are associated partially with the expression of pro-inflammatory genes in the mucosa, which may result to colorectal cancer in the future (42). Several molecular and chromosomal differences have been reported (43)(44)(45)(46)(47), while chromosomal instability has been detected in approximately 30% of the right colon cancer and 70% of left colon cancer (48,49). The median age of patients with right colon cancer is higher compared to patients with left colon cancer, while a greater proportion of patients with right colon cancer are females (44,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is different (39)(40)(41), and recently published data has shown that colorectal cancerassociated bacterial clusters are differentially correlated with mucosal gene expression profiles, while a few clusters are associated partially with the expression of pro-inflammatory genes in the mucosa, which may result to colorectal cancer in the future (42). Several molecular and chromosomal differences have been reported (43)(44)(45)(46)(47), while chromosomal instability has been detected in approximately 30% of the right colon cancer and 70% of left colon cancer (48,49). The median age of patients with right colon cancer is higher compared to patients with left colon cancer, while a greater proportion of patients with right colon cancer are females (44,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is different [ 46 , 47 , 48 ], and recently published data have shown that colorectal cancer-associated bacterial clusters are differentially correlated with mucosal gene expression profiles, while a few clusters are partially associated with the expression of pro-inflammatory genes in the mucosa, which may result in colorectal cancer in the future [ 49 ]. Several molecular and chromosomal differences have been reported [ 50 , 51 , 52 , 53 , 54 ], while chromosomal instability has been detected in approximately 30% of cases of right colon cancer and 70% of cases of left colon cancer [ 55 , 56 ]. The median age of patients with right colon cancer is higher compared to patients with left colon cancer, while a greater proportion of patients with right colon cancer are females [ 51 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical methods frequently offer symptom relief and a better quality of life. Emerging treatments, including cabozantinib, show promise, but the efficacy of targeted treatments on bone health is still under review ( 23 , 24 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%